The Role of Information Technologies in Teaching Foreign Languages (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the use of modern technologies in teaching foreign languages offers many opportunities to make teaching more interesting and more effective in terms of improvement. In addition, this modern technological tool attracts students based on their interests ideas are included to help you learn and do.